Analysis Of Labor Absorption In East Nusa Tenggara Province 2016-2020 Period - Novi T Kiak; Marselina Ratu; Maria I. H. Tiwu; Olivia Louise Eunike Tomasowa (Green Publisher Indonesia, 2022)
This study analyzes the absorption of labor in East Nusa Tenggara Province for the 2016-2020 period. The research aims to identify sectors that have the power to absorb labor and the ability to compete in the 2016-2020 period; and find out how the effect of economic growth on employment in East Nusa Tenggara Province for the 2016-2020 period. The type of secondary data was obtained during the 2016-2020 observation period. These data include GRDP based on constant prices in East Nusa Tenggara Province for the 2016-2020 period and population data for those aged 15 years and over (labor data). The analytical tools used are Location Quotient (LQ), Shift Share (SS), Kindergarten Productivity, TK Elasticity, MRP, Klassen and Typology. The results of the LQ analysis show that the agricultural, forestry and fisheries sectors are sectors that are not the leading sectors in absorbing labor during that period, the study because it has an LQ value below 1. The results of the analysis that the shift-share analysis shows during the analysis period 2016 to by 2020. In the province of East Nusa Tenggara, the largest information and communication sector has the largest competitive advantage, which is indicated by having a higher nij value compared to other provinces sector and has the largest number of employees.